Stress granules in cancer: Adaptive dynamics and therapeutic implications - Yunlu Jia; Ruyin Jia; Zhengfeng Dai; Jianbiao Zhou; Jian Ruan; WeeJoo Chng; Zhen Cai; Xiaochen Zhang (iScience, 2024)
Summary: Stress granules (SGs), membrane-less cellular organelles formed via liquid-liquid phase separation, are central to how cells adapt to various stress conditions, including endoplasmic reticulum stress, nutrient scarcity, and hypoxia. Recent studies have underscored a significant link between SGs and the process of tumorigenesis, highlighting that proteins, associated components, and signaling pathways that facilitate SG formation are often upregulated in cancer. SGs play a key role in enhancing tumor cell proliferation, invasion, and migration, while also inhibiting apoptosis, facilitating immune evasion, and driving metabolic reprogramming through multiple mechanisms. Furthermore, SGs have been identified as crucial elements in the development of resistance against chemotherapy, immunotherapy, and radiotherapy across a variety of cancer types. This review delves into the complex role of SGs in cancer development and resistance, bringing together the latest progress in the field and exploring new avenues for therapeutic intervention.